Plasticity of stingless bee Melipona fuliginosa Lepeletier to obtain food resources in Amazonia - Costa, Luciano; Galaschi-Teixeira, Juliana Stephanie; Maia, Ulysses Madureira; Imperatriz-Fonseca, Vera Lucia (Sociobiology, 2018)
The stingless bee Melipona fuliginosa Lepeletier is described as being aggressive robber, but there is little information about its raids. Here, we describe two different raids of M. fuliginosa on other Melipona species: Melipona paraensis Ducke and Melipona fasciculata Smith. The robbing behavior was observed in the Volta Grande do Xingu region (Pará) and Carajás National Forest (Pará), and the attacks by M. fuliginosa occurred at the end of the dry season, shortly before the start of the rainy season, a time of flower scarcity. The raid on M. paraensis hive lasted five days and involved no deaths of worker bees of both species; the robbers collected honey and wax. During the pillaging, M. fuliginosa workers dedicated themselves exclusively to this task; their flight activity peaked between 8:00 a.m. and 12:00 p.m. but lasted until 6:00 p.m, which is atypical for the species. The raid on M. fasciculata differed from the other event because it led to the extermination of all forager workers of fi ve colonies, however, the brood combs as well as the callow workers were preserved; the robbers collected honey and wax. M. fuliginosa attack defensive and non-defensive colonies, the events can cause severe damage and may lead to death of the victim colony in natural conditions. Flight activity varies from foraging on fl owers during dawn to all day long robbing, showing considerable plasticity to obtain food resources. Robbing behavior could be associated to fl ower scarcity and artificial feeding.